Burden of Caring in Schizophrenia: A Bibliometric Analysis. - Doner, Seher; Yilmaz, Sevil (International Journal of Caring Sciences)
Background: Patients with schizophrenia cannot fully fulfil their roles in the society and family due to the cognitive losses, disability, economic and social problems they experience, and they need the care and support of someone else. This may cause burden on the caregivers. Aim: The aim of this study is to bibliometrically analyse the trends in the studies related to the burden of care of individuals caring for schizophrenia patients. Methodology: This study is a descriptive study based on bibliometric analysis of the literature database. The data were obtained from a literature search on the Web of Science (WoS) database using the keywords 'schizophrenia' and 'burden of care'. The 752 data that met the inclusion criteria were analysed. In the bibliometric data analysis, the data obtained from the WoS database, WoS analysis reports and VOSviewer software were used for data analysis and visualisation. Results: The articles analysed were published in many different categories, more than half of them were in the psychiatry category, with the nursing category coming in second place. According to the most frequently used keywords, schizophrenia and carer burden are especially focused on families, and quality of life, coping and emotional expression are also highly researched topics. Psychoeducation has also been used as part of the research. Recently, especially anxiety, depression, stress, social support, psychosocial intervention have been focused on the axis. Conclusion: The issue of care burden of individuals caring for schizophrenia patients is a current issue that continues to be studied with increasing number from past to present. In this study, a general perspective on the subject was presented and thematic issues were determined. The results of the study may guide future research on the burden of care of individuals caring for schizophrenia patients.